Perrotta Hypersexuality Questionnaire (PeHy-Q): Development, regulation and validation of a new psychometric instrument for the diagnosis of hypersexuality - Giulio Perrotta (Annals of Psychiatry and Treatment - Peertechz Publications, 2023)
Introduction: The clinically relevant condition of hypersexuality is to date nebulous in its definition, and although it is understood as a psychological and behavioural alteration as a result of which sexually motivated stimuli are inappropriately sought and often experienced in a way that is not entirely satisfactory, it is unclear whether it is an obsessive disorder or is a trait of a more complex personality disorder or a consequence arising from a medical condition, whether primary or secondary.  Methods: Using the Perrotta Hypersexuality Global Spectrum of Gradation (PH-GSS) as a model, the clinical and control population was selected to validate a new psychometric test, then compared with the Sexual Addiction Screening Test (SAST-R, v. 2.0).  Results: Statistical analysis showed that the new psychometric test has a well-defined and stable construct (R = 0.975; p = 0.000), the variables are well represented (R = 0.999; p = 0.000) and it is positively correlated with the other constructs already validated (R = 0.951; p = 0.000).  Conclusions: Perrotta Hypersexuality Questionnaire (PeHy-Q) is a valid, efficient, and effective psychometric tool to diagnose the clinically relevant condition of hypersexuality to improve the structural and functional framing of the patient and the appropriate therapy to pursue.